Arthur White Collection, Correspondence from London division via Bonnie Angelo to Time Publetter, July 22, 1978. - Angelo, Bonnie (Time Magazine; Digitized from original print, Valdosta State University Archives and Special Collections, December 6, 2016., 1978)
Correspondence from London division via Bonnie Angelo to Time Publetter in reference to the impending birth of the first "test-tube baby" by Lesley and John Brown in Oldham, England in 1978 by doctors Patrick Steptoe (Gynecologist) and Robert Edwards (Physiologist).
Digitized from original print, Valdosta State University Archives and Special Collections, December 6, 2016.
Keywords: Test tube baby; In Vitro Fertilization; IVF; Steptoe-Edwards Fertilization Technique; Time Magazine; Time Publetter; Arthur White; Lesley Brown; John Brown; Lousie Joy Brown; Patrick Steptoe; Professor Sir Robert Edwards; Robert Edwards; Oldham General Hospital; Oldham, England; London, England; England; Great Britain; 1970s; 1978; Bonnie Angelo